THE RISE OF MULTINATIONAL CORPORATION AND THE DEAD OF INNOVATION: A Interdiscipline Approach - Solihin, Mohamad (AS-SALAM, 2013)
The article presents the rise of multinational corporation effect towardinnovation in globalization era and how islamic economics viewsthemâas an alternative perspective in analyzing this problem. âTherise of multinational corporatian reduces the product innovationâ. It is aassumption and appears as an interpretation to market-mechanism. Thethesis will elaborate in the paper. It means that innovation reduction iscaused by multinational corporation product following market trend. Thethesis, indeed, corrobates John Xiros Cooperâs theory. âThe market is simplyan economic mechanism which has no extraordinary powers to shift theground of thinking and knowing in any general sense. It is merely, they willsay, a mechanism for allocating resources among producers, a mechanismfor the setting of commodity prices, for distributing goods, for adding value,for raising capital to sustain enterprise, and so on.â Wrote Xiros Cooper.To understand the reason why multinational corporation rising makesinnovation weak will use sociological approach, especially epistemology ofmarketâXiros Cooper theory.Keywords : MNC (multinational corporat), market mechanism, marketculture and innovation.